2017
DOI: 10.1038/srep43779
|View full text |Cite
|
Sign up to set email alerts
|

A new malaria vector mosquito in South Africa

Abstract: South Africa aims to eliminate malaria within its borders by 2018. Despite well-coordinated provincial vector control programmes that are based on indoor residual insecticide spraying, low-level residual malaria transmission continues in the low-altitude border regions of the north-eastern sector of the country. In order to identify the underlying causes of residual transmission, an enhanced vector surveillance system has been implemented at selected sites in the Mpumalanga and KwaZulu-Natal (KZN) provinces. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 17 publications
3
77
0
Order By: Relevance
“…This approach is a better approximation to how the traps would be deployed for surveillance compared to targeting only sites with high numbers of mosquitoes. Despite this, the CDC trap collected 7.4 females per night while the net trap collected 8.6 females per night, similar to previous collection efforts in KNP that report aggregated data, with a median of 31 (range 17-116) females across three net traps and a median of 19 (range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] in three CDC traps [15]. Based on this data, the consistent patterns of community composition and largely consistent patterns of abundance between traps suggest that comparisons between studies using these two methods are possible.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This approach is a better approximation to how the traps would be deployed for surveillance compared to targeting only sites with high numbers of mosquitoes. Despite this, the CDC trap collected 7.4 females per night while the net trap collected 8.6 females per night, similar to previous collection efforts in KNP that report aggregated data, with a median of 31 (range 17-116) females across three net traps and a median of 19 (range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] in three CDC traps [15]. Based on this data, the consistent patterns of community composition and largely consistent patterns of abundance between traps suggest that comparisons between studies using these two methods are possible.…”
Section: Discussionsupporting
confidence: 72%
“…Chikungunya and dengue fever outbreaks are less common in South Africa [14], but we describe the distribution of their vector, Ae. aegypti [22], because additional known prime vectors in Africa were not found (Ae. africanus, Ae.…”
Section: Describing Regional Patterns Of Disease Vectorsmentioning
confidence: 99%
“…Currently in KZN, larval source management is employed in an ad hoc uncoordinated manner. The KZN control programme should consider upscaling its use; guided by regularly updated breeding site maps and comprehensive data management, to control out-door resting vector populations associated with sustaining residual transmission in KZN [15,40]. As vector populations with reduced susceptibility to pyrethroids were detected in this study and have been confirmed in neighbouring Mozambique [41], it is imperative that resistance susceptibility testing becomes a routine programmatic activity, with the data generated used to inform insecticide selection.…”
Section: Discussionmentioning
confidence: 90%
“…Of the Anopheles funestus group, the species identified by PCR assays was An. vaneedeni, a secondary vector for malaria in the region (Burke et al 2017). There was a significant difference between locality and mosquito abundance for the seven widely distributed potential vectors of arboviruses with the Chi‐Square test P ‐value for all species being <0.001).…”
Section: Resultsmentioning
confidence: 99%
“…vaneedeni (a member of the An. funestus group) playing a secondary role (Burke et al 2017). Nevertheless, this information is of importance and value from a public health perspective in creating awareness among health department officials and tourism operators regarding the potential for malaria transmission.…”
Section: Discussionmentioning
confidence: 99%